Diagnóstico ambiental de metais no sedimento de córregos adjacentes a áreas de cultivo de banana (Musa Spp.) no estado de São Paulo, Brasil - Corbi, Juliano José (2013)
The State of São Paulo is the great banana producer with 1.17 million tons per year. In this area, 33.113 ha are destined to the production of 810.000 tons of banana. The use fertilizers in the banana plant cultivation, in addition with deforestation of riparian vegetation are responsible for impacts on the hydric resources. This work deals with the possible impact of banana activity in the sediments of 10 streams by the study of 7 metals (Cd, Cu, Zn, Fe, Mn, Cr and Ni). The results show that there is a higher concentration of metals in streams with banana cultivation than forested streams. Although, with exception of Ni, the values of metals detected are above to the Threshold Effect Level (TEL) and the Probable Effect Level (PEL) for sediments.